Direct to market or centralised distribution? A regional supply chain optimisation strategy - ZELLER, Alan (Institutional Knowledge at Singapore Management University, 2024)
The case illustrates the benefits of distribution pooling for a company struggling with high inventory and write-off costs. It compares two distribution networks – one with direct shipments from a factory in Canada to markets in Southeast Asia, and the other using a regional distribution centre (RDC) in Singapore. The case’s protagonist is Janet Chua, a supply chain director at Genova, a multinational pharmaceutical company. She needs to analyse these two distribution models, weigh the pros and cons, and recommend the best option to her senior management. Her analysis includes weighing the transportation, inventory, write-offs, and financing costs for both models while considering the impact on lead times, service levels, and other factors such as sustainability. Through her analysis, Janet would have to demonstrate that optimising the supply chain network can circumvent constraints on shelf-life and minimum order quantity. More importantly, this shift must unlock the company’s growth potential by reinvesting cost savings into marketing, thereby boosting sales and profitability. Given these considerations, should she recommend switching to the RDC? Students will learn to identify the inefficiencies of using a direct factory-to-market model, especially for products with minimum order quantity and short shelf life. By considering supply chain and business profitability perspectives, they will evaluate the advantages and disadvantages of using a regional distribution centre. They will then determine the conditions under which switching from a factory-to-market model to a regional distribution centre model would be beneficial.